Youth Educational Project “Student+”: Implementation Results - Umnyashova, I.B. (Bulletin of Practical Psychology of Education, 2021)
The article presents the results of the implementation of the Youth educational project “Student+” by the Russian Public Organization “Federation of Psychologists of Education of Russia” — the winner of the competitive selection of applications from socially oriented non-profit organizations for the grant of the Mayor of Moscow in 2019 in the category “Volunteering”. The “Student+” project was created with the aim of involving university and college students in volunteer activities aimed at preventing negative phenomena in the youth environment, including primary prevention of chemical addiction among student youth. The main principle of the implementation of the prevention of drug addiction and alcoholism among students, implemented in the Project “Student+”, is the principle “an equal teaches an equal”, which involves special training of student volunteers in the design of preventive measures and scientific and methodological support during the implementation by students of copyright classes with the participation of peers. During the implementation period of the “Student+” Project (October 2019 — September 2020), a program of educational activities was developed and tested, aimed at developing skills in the field of primary prevention of illegal consumption of narcotic drugs and psychotropic substances in the student environment; content of the program, including for distance learning (website студентплюс.рф); methodological recommendations for universities on the organization of primary prevention of illegal consumption of narcotic drugs and psychotropic substances in the student environment, based on the principle “an equal teaches an equal”. В статье представлены итоги реализации Общероссийской общественной организацией «Федерация психологов образования России» Молодежного просветительского проекта «Студент+» — победителя конкурсного отбора заявок социально ориентированных не-коммерческих организаций для предоставления гранта Мэра Москвы в 2019 году в номи-нации «Добровольчество и волонтерство». Проект «Студент+» создан с целью вовле-чения студентов вузов и колледжей в волонтерскую деятельность, направленную на профилактику негативных явлений в молодежной среде, в том числе проведение первич-ной профилактики химической аддикции среди студенческой молодежи. Основным прин-ципом реализации профилактики наркомании и алкоголизма среди студентов, реализуе-мым в проекте «Студент+», является принцип «Равный обучает равного», предпола-гающий специальную подготовку студентов-волонтеров в области проектирования профилактических мероприятий и научно-методическую поддержку во время реализации студентами авторских занятий с участием сверстников. За период реализации проекта «Студент+» (октябрь 2019 — сентябрь 2020 года) были разработаны и апробированы программа просветительских мероприятий, направленная на развитие навыков в облас-ти первичной профилактики незаконного потребления наркотических средств и психо-тропных веществ в студенческой среде; контент программы, в том числе для дистан-ционного обучения (сайт студентплюс.рф); методические рекомендации для вузов по ор-ганизации первичной профилактики незаконного потребления наркотических средств и психотропных веществ в студенческой среде, основанной на принципе «Равный обучает равного».